The Little Penguin (Eudyptula minor) as an indicator of coastal trace metal pollution - Finger, Annett; Lavers, Jennifer L.; Dann, Peter; Nugegoda, Dayanthi; Orbell, John D.; Robertson, Bruce; Scarpaci, Carol (Environmental pollution (1987), 2015)
Monitoring trace metal and metalloid concentrations in marine animals is important for their conservation and could also reliably reflect pollution levels in their marine ecosystems. Concentrations vary across tissue types, with implications for reliable monitoring. We sampled blood and moulted feathers of the Little Penguin (Eudyptula minor) from three distinct colonies, which are subject to varying levels of anthropogenic impact. Non-essential trace metal and metalloid concentrations in Little Penguins were clearly linked to the level of industrialisation adjacent to the respective foraging zones. This trend was more distinct in blood than in moulted feathers, although we found a clear correlation between blood and feathers for mercury, lead and iron. This study represents the first reported examination of trace metals and metalloids in the blood of any penguin species and demonstrates that this high trophic feeder is an effective bioindicator of coastal pollution. •Trace metals measured in blood and feathers.•Arsenic, Mercury and Lead significantly higher at urban colony.•Correlations found between trace metals in feathers and blood.•Little Penguins are suitable bioindicators for coastal metal pollution. This study confirms the suitability of the Little Penguin as a bioindicator of coastal metal pollution in coastal areas using non-destructive sampling methods.